Development Of Interactive Worksheet-Based Learning Media For English Lessons For Fourth-Grade Students At Alam Mutiara Umat Elementary School - Fairus Malika Khoirunnisa; Dina Kartikawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Interactive Worksheets are a digital learning tool designed to facilitate students’ active participation in the learning process through a variety of interactive activities, including matching vocabulary with images, listening exercises, sentence completion, and context based tasks. This study aims to describe the development process and evaluate the feasibility of interactive worksheet-based learning media for English lessons for fourth-grade students at Alam Mutiara Umat Elementary School. The media was developed using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The product was designed to support English language learning through interactive activities such as matching vocabulary with pictures, listening exercises, completing sentences, and word-matching tasks. The participants involved in this study were 28 fourth-grade students. Data were collected through expert validation, classroom observations, student interviews, questionnaires, and post-implementation test results. The findings showed that the developed interactive worksheet was categorized as very valid based on material and media expert evaluations. In addition, students demonstrated positive responses toward the media, indicating increased participation, learning motivation, and engagement during classroom activities. Therefore, the interactive worksheet is considered a feasible and effective alternative medium for supporting English language learning at the elementary school level.